Analisis Sifat Fisika Kimia Tanah dan Uji Daya Hambatnya terhadap Bakteri Air Liur AnjingLiar - Sjamsiah, Sjamsiah; Arifuddin, Arifuddin; Masri, Mashuri; Sappewali, Sappewali; Islamiah, Indah; Hamrullah, Hardiyanti; Nesti, Elmika (Al-Kimia, 2019)
This study aims to analyze the physical and chemical properties of soil from paddy fields, garden lands and city area also determine the soil inhibitory test of dog saliva bacteria. The results showed that these three soil types have different physical chemical properties and have different inhibitory zones against dog saliva bacteria. The physical chemistry of soil from paddy fields, garden lands and city area (0 cm) are as follows: for color; dark chocolate; grayish brown; and blackish ash, for texture: clay; clay; and sandy clay, for moisture content: 7.14; 6.53; 2.13. for pH close to neutral around 6.52-7.03; Total N is low (0.08-0.23); organic C compounds are classified as moderate; nutrient content of Ca/Mg is classified as moderate (9.55 /1.70 - 14.89/2.22); cation exchange capacity is classified as high (25.32-29.03) in paddy fields and gardens and compounds. The inhibitory zone of the highest dog saliva bacteria is in garden soil (3.7 cm), then paddy soil (2.86 cm) and land in the city area (1.6 cm).